2021
DOI: 10.1093/tropej/fmab078
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Manifestations Associated with Parvovirus B19 Infection in Immunocompetent Children: Case Series and Systematic Review

Abstract: An increasing number of reports have described human parvovirus B19 infection in association with a variety of neurological manifestations, especially in children. This study assessed the clinical and laboratory outcomes found in a case series of immunocompetent children who tested positive for parvovirus B19 by qualitative polymerase chain reaction assays of cerebrospinal fluid, in a tertiary referral center in the western Brazilian Amazon. We screened 178 children with clinically diagnosed central nervous sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 72 publications
4
8
1
Order By: Relevance
“…Her CSF also revealed pleocytosis with increased protein and lactate, and normal glucose levels. These findings are in agreement with prior descriptions of Parvovirus B19 CNS infection [14], [28], [29], [30]. In blood tests, a decrease in hemoglobin with levels below 10 g/dL, and anisocytosis was observed , as reported in the literature [14], [31,32].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Her CSF also revealed pleocytosis with increased protein and lactate, and normal glucose levels. These findings are in agreement with prior descriptions of Parvovirus B19 CNS infection [14], [28], [29], [30]. In blood tests, a decrease in hemoglobin with levels below 10 g/dL, and anisocytosis was observed , as reported in the literature [14], [31,32].…”
Section: Discussionsupporting
confidence: 93%
“…In our series of 600 CSF samples from acute CNS infections B19 was identified in only a single sample (0.17%). In other case series, this virus has been identified as a pathogen associated with undiagnosed meningoencephalitis, reaching a prevalence rate of up to 4.3% [14], [26], [27] , a frequency higher than that obtained in our series.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…8,11 Moreover, a case of PVB19 encephalitis has been reported with normal MRI brain findings. 1 Systematic review and case series analysis in immunocompetent children with neurological manifestations of PVB19 by Monteiro et al 2 have not found any objective assessment of the efficacy of IVIG and/ or steroids for therapy. This has been consistent with other reviews by Barah et al 5 and Watanabe et al 6 However, several cases have noted clinical improvement in children with PVB19-associated neurological symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In the breeding industry, goose parvovirus often causes huge economic losses due to large-scale epidemic in different regions [ 2 ]. Pregnant women are susceptible to human parvovirus B19, and it can be transmitted to the fetus after infection causing aplastic anemia[ 3 5 ]. Parvoviruses are important pathogens leading to animal diseases and have a significant role in gene therapy, oncolytic therapy, vaccine development, and as passive immune vectors [ 6 ].…”
Section: Introductionmentioning
confidence: 99%